Maré de lazer: construções, sociabilidades e significados dos lugares de lazer no Morro do Timbau - Diogo Silva do Nascimento (2020)
This doctoral thesis investigated the stories of leisure spaces in Morro do Timbau (Bairro Maré - Rio de Janeiro), from 1931 to 1974, based on the residents' memory and records. The way in which local memories, sociability and identities woven through the experiences fostered in these leisure spaces were investigated. In addition, the work sought to investigate the ways in which collective arrangements were woven through bonds of friendship, conflict and territoriality from living in the fields, streets, blocks and alternative spaces of the favela that functioned as leisure areas. The research used the qualitative approach through narrative interviews, analysis of photos and documents. Thus, the work pointed to the importance of giving voice to the experiences that, in a sociocultural context, built “multiple social worlds” in which individuality and subjectivity were closely linked to the experiences of building this territory historically stigmatized by violence.